Integration of Religious Moderation Values in Islamic Religious Education Learning: Efforts to Build Religious Tolerance in Students at SMK Indonesia Membangun 2 Medan - Sari Wahyuni Siregar; Ismaraidha Ismaraidha (Ikatan Cendikiawan Ilmu Pendidikan Islam (ICIPI), 2025)
Phenomena such as inter-religious prejudice, exclusive attitudes, and lack of understanding of diversity often emerge in students' social interactions, which are challenges in the world of education, especially in multicultural school environments. This study aims to analyze how the integration of religious moderation values ​​in Islamic Religious Education learning can contribute to building religious tolerance among students at SMK Indonesia Membangun 2 Medan. The research method used is descriptive qualitative with a phenomenological approach. Data collection techniques using observation, interviews, and documentation. Data analysis techniques through the stages: data condensation, data presentation, and drawing conclusions and verification. The results of this study indicate that the integration of religious moderation values ​​in Islamic Religious Education learning at SMK Indonesia Membangun 2 Medan is carried out through a contextual, dialogical, and reflective learning approach. This approach has been successful and impactful in fostering an attitude of tolerance, openness to differences, and the ability to live side by side peacefully in a pluralistic environment. Changes in student behavior that are evident in daily interactions, such as respecting the religious practices of others, refraining from prejudice, and being active in interfaith collaboration, are evidence of the success of learning based on moderation values.